Economies of Scale and the Size of Exporters. Issue 3 (1st June 2015) - Armenter, Roc; Koren, Miklós
Abstract: How important are economies of scale in exporting? We argue that firm size cannot be the main determinant of export status if a model is to be consistent with the observed number and size of exporters. Instead, we need a lot of variation independent of firm size to reconcile the model with the data. We show that the augmented model also has markedly different implications regarding the margin of adjustment in the event of a trade liberalization: most of the adjustment is through the intensive margin and productivity gains due to reallocation are halved.